Altered blood flow in cerebral perforating arteries of rat models of diabetes: A synchrotron radiation microangiographic study toward clinical evaluation of white matter hyperintensities. (December 2015) - Fukuyama, Naoto; Tsukamoto, Yuko; Takizawa, Shunya; Ikeya, Yoshimori; Fujii, Toshiharu; Shinozaki, Yoshiro; Takahari, Yoko; Kawabe, Noboru; Wakana, Noriaki; Umetani, Keiji; Todoroki, Kikue; Fukui, Sayato; et al.
Abstract : Aim: As altered blood flow in the cerebral perforating arteries (PA) might be related to development of cerebral white matter hyperintensities, we examined whether the hemodynamic relationship of the PA and middle cerebral artery (MCA) is altered in rat models of diabetes, compared with normal rats and a rat model of sinoatrial denervation (blood pressure fluctuation model). Methods: We used microangiography with monochromatic synchrotron radiation to measure the diameters of the PA and MCA at 4.5 μm resolution in five groups of rats: (i) Long‐Evans Tokushima Otsuka (LETO); (ii) Otsuka Long‐Evans Tokushima Fatty (a model of type 2 diabetes with obesity); (iii) LETO with sinoaortic denervation (LETO + SAD); (iv) F344; and (v) F344 + streptozotocin (a model of type 1 diabetes). Results: Compared with LETO, Otsuka Long‐Evans Tokushima Fatty rats showed a significant reduction in the diameter of both PA and MCA, though the PA/MCA diameter ratio was unchanged. In contrast, compared with LETO, LETO + SAD rats showed an increased MCA diameter, and the PA/MCA diameter ratio was decreased. Compared with F344 rats, the MCA diameter was increased in F344 + streptozotocin rats, and the PA/MCA diameter ratio was decreased. Scatter diagrams showed that the diameters of the PA and MCA were essentially independent of each other in the two types of diabetic models. Conclusion: PA were consistently visualized at high resolution by means of microangiography using synchrotron radiation. The present results show that rat diabetic models exhibit changes in PA diameter and PA/MCA diameter ratio, which might be related to the development of diabetes‐associated cerebral white matter hyperintensities. Geriatr Gerontol Int 2015; 15 (Suppl. 1): 74–80.